HERMENEUTIKA SEBAGAI PENDEKATAN DALAM KAJIAN ISLAM - Hariyanto Hariyanto (LP2M Universitas Ibrahimy, 2017)
The Qur'an as kalamullah descended to the Prophet Muhammad through the angel Gabriel as a miracle. The Qur'an is used as a guide for life for humans. To find the guidelines contained in it, the Qur'an is not only used as a readable scripture, but we must also understand the content of its meaning. The understanding of the content of Al-Qur'an content has been done by some great scholars. This understanding is done through several approaches, among others, with a hermeneutic approach. The presence of hermeneutics can’t be separated from the growth and advancement of thinking about language in the discourse of philosophy and other scholarship. Hermeneutics as a method of reading the text has been widely recognized in various fields of traditional Islamic scholarship, especially in the tradition of Fiqh and Tafsir al-Qur'an. Meanwhile, modern hermeneutics Islamic of ideology can basically be called a big leap in the formulating the methodology of Islamic ideoogy in general and the method of interpretation of the Qur'an in particular.